Trem di Pasuruan akhir abad XIX dan potensinya sebagai media pembelajaran sejarah - Davia Faringggasari; Daya Negri Wijaya (Universitas Negeri Malang, 2023)
This study aims to describe the tram in Pasuruan in the late 19th century and its potential as a media for learning history. The authors use historical research methods which are divided into five stages, namely topic selection, source collection, historical criticism, interpretation and historiography. The results of this study show that the construction and operation of trams was one of the solutions of the Dutch government to transportation problems related to the transportation and distribution of plantation products in the Pasuruan region at the end of the 19th century. The existence of trams in Pasuruan was considered to be able to solve the deadlock of mass transportation in Pasuruan. As an effort to attract students' interest in learning, the historical content of trams in Pasuruan at the end of the 19th century was able to be packaged using a variety of interesting technology-based learning media including Infographics, documentaries, animated videos, Comics, Educational Ladder Snakes. Researchers also offer other learning media, namely LEACO (Qr-Code-based Leaflet). Kajian ini bertujuan untuk mendeskripsikan trem di Pasuruan akhir abad XIX dan potensinya sebagai media pembelajaran sejarah. Penulis menggunakan metode penelitian sejarah yang dibagi menjadi lima tahapan yakni pemilihan topik, pengumpulan sumber, kritik sejarah, interprestasi dan historiografi. Hasil dari kajian ini menunjukan bahwa pembangunan dan pengoperasian trem merupakan salah satu solusi dari pemerintah Belanda terhadap permasalahan transportasi terkait pengangkutan dan pendistribusian barang hasil perkebunan di wilayah Pasuruan pada akhir abad XIX. Keberadaan trem di Pasuruan dianggap mampu memecahkan terkait kebuntuan angkutan massal di Pasuruan. Sebagai upaya untuk menarik minat belajar siswa, konten sejarah trem di Pasuruan akhir abad XIX dapat dikemas menggunakan berbagai media pembelajaran yang menarik berbasis teknologi meliputi Infografis, film dokumenter, video animasi, Komik, Ular Tangga Edukatif. Peneliti juga menawarkan media pembelajaran lainnya yaitu LEACO (Leaflet berbasis Qr-Code).